PRESERVING TRADITIONAL KNOWLEDGE AND FOLKTALE THROUGH TEXT DOCUMENTATION: A CASE STUDY OF PRESERVING FOLKTALE OF PLUNTURAN VILLAGE PONOROGO - YB Agung Prasaja; Tri Pramesti; Muizzu Nurhadi; Pariyanto Pariyanto; Mateus Rudi Supsiadji (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The maintenance and preservation of Indonesian traditional knowledge and folklore is urgently needed. Traditional knowledge and folktale are cultural heritages that provide intangible wealth for Indonesia. This paper provides a brief analysis of the traditional values transmitted by our folktales and the functions served by local legends and myths in Plunturan society. This paper offers some practical recommendations for collecting our folktales, myths, and legends in the form of text using the currently available digital technology to create the first comprehensive and dynamic Plunturan folktales. This community service focuses on the problems that can arise when documenting folklore and traditional knowledge. what solutions should be done to overcome these problems. The method used in this study is by interviewing the resource person. The results of this study conclude that text documentation needs to be done to preserve folklore and traditional knowledge.Keywords: Traditional knowledge, Folktales, Plunturan, Documenting